Migration of PAHs and Phthalates from Package Materials during Water Storage: Glass or Plastic?. (14th February 2022) - Khaustov, Aleksandr; Redina, Margarita; Goryainov, Sergey
Abstract: The quality of drinking and mineral waters has traditionally been assessed in terms of the presence of useful components and the absence of undesirable impurities in the natural source. However, the contact with the packaging material when bottling or storing samples can change the composition of the water, introducing toxic compounds of anthropogenic nature. The processes of absorption of certain groups of chemical compounds from solutions by packaging materials are also possible. Water is a non-equilibrium geochemical system, which suggests changes in its composition depending on various factors. Therefore, it was of key importance to evaluate the interaction of different types of water with the similar types of packages. The research presents the results of our experiments on the assessment of package materials impact (glass and PET) on the water quality. Past research discusses characteristics of different polyethylenes as packaging materials at large. However, few investigations contain the quantitative assessments of the entry of hazardous substances from polyethylene into food products, or vice versa—the absorption of hazardous components by plastic. This research focuses on changes in the composition of a complex of polycyclic aromatic hydrocarbons (PAHs) in water samples taken on the Kerch Peninsula in close proximity to the unique balneological object—Lake Chokrak. Besides, the investigation presents the qualitative analysis of the popular light drinking water in glass bottles. The change in water composition is partly determined by the characteristics of the waters themselves; nevertheless, the effect of the packages on changes in water quality is clearly demonstrated. There is a demand for specific attention and an individual approach to choosing packaging materials for bottling water, especially for drinking and medical use, as well as when organizing the collection and storage of water samples for specific pollutants.